Portable 3D Gait Analysis Assessment in MTT Treat Chronic Ankle Instability: A Retrospective Study. (7th June 2021) - Song, Yujuan; Xu, Sibai; Dai, Yanqiu; Jia, Jun; Liu, Hebin; Li, Zhenjing
Abstract : Purpose . Retrospective analysis of the effect of portable 3D gait analysis as an innovative evaluation method in the treatment with MTT on chronic ankle instability patient. Methods . From January 1, 2019, to December 31, 2019, 56 cases of chronic ankle instability (CAI) were extracted from the medical record system of Shenzhen Longhua District Central Hospital. All the patients of 56 cases accepted the medical training therapy (MTT). As outcome parameters, the alterations of the Cumberland ankle instability tool (CAIT), foot and ankle ability measure (FAAM), were used before the treatment and after treatment; meanwhile, the portable apparatus 3D gait analysis was used to measure the gait parameters. Conclusion . The results showed only ankle angle parameters Y -axis, maximum dorsiflexion during support period (°) had a significant difference, and the p value is 0.039. Meanwhile, the CAIT, FAAM, and most 3D gait analysis data had no significant difference. This particular statistical difference shows that CAI can be measured scientifically and objectively, although most measurement parameters have no change. These results make further reveal that the CAI patients are suffering with dynamic abnormality of ankle motion angle; this also provides us with a measurable and systematic evaluation reference plan for CAI treatment in the future.